2009
DOI: 10.1002/chem.200802458
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II) Complexes for the Efficient Catalytic Asymmetric Transfer Hydrogenation of Ketones

Abstract: Iron(II) carbonyl compounds of the type trans-[Fe(NCMe)(CO)(P-N-N-P)][BF(4)](2) bearing the ethylenediamine-derived diiminodiphosphine ligands (R,R)- or (S,S)-1,2-diphenyl-1,2-diaminoethane were synthesized and characterized, including by their crystal structures. The new complexes are suitable precatalysts for the transfer hydrogenation of ketones at room temperature, giving turnover frequencies of up to 2600 h(-1) with low catalyst loadings (0.025-0.17%). Screening experiments showed that the precatalysts ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(82 citation statements)
references
References 32 publications
1
81
0
Order By: Relevance
“…[1] Clearly, most of the work in organometallic catalysis has been performed by applying noble metals based on palladium, rhodium, iridium, and ruthenium complexes. [6][7][8][9][10][11][12][13][14][15][16][17] To date, most of the work in this field has demonstrated that iron complexes can be used in the same way as noble metal catalysts. In this respect, homogeneous catalysis with iron complexes offers a highly attractive substitute.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Clearly, most of the work in organometallic catalysis has been performed by applying noble metals based on palladium, rhodium, iridium, and ruthenium complexes. [6][7][8][9][10][11][12][13][14][15][16][17] To date, most of the work in this field has demonstrated that iron complexes can be used in the same way as noble metal catalysts. In this respect, homogeneous catalysis with iron complexes offers a highly attractive substitute.…”
Section: Introductionmentioning
confidence: 99%
“…The latter assignment is in agreement with the 31 P chemical shift value (δ =19.00 ppm) determined for an authentic sample of 5, which had previously been obtained by a different route. [6] The solid-state IR spectrum of the reaction mixture (KBr disc; Figure S3, Supporting Information) has two strong signals in the diagnostic region, [14,15] at 2060 and 2015 cm -1 , which we assign to the symmetric and asymmetric CO stretching modes, respectively, of the cis-dicarbonyl complex 4. The stretching of the CO bond for one carbonyl ligand lowers its π* orbital energy and thus favours backdonation from the metal ion.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, when complexes 71, 72 72 73 and 73 74 were used in these processes, the corresponding chiral alcohols were produced with variable results. Similar results were also obtained with other type of iron derivatives, such as bisisonitrile iron complexes 74.…”
Section: Iron Catalystsmentioning
confidence: 99%